KINETIKA HIDROLISIS TRIGLISERIDA RBDPO MENJADI CAMPURAN ASAM LEMAK - Alamsyah, Andi Nur (Universitas Diponegoro, 2012)
Indonesia is one of largest producer of vegetable oils especially palm oil. The Palm oil commodity is potential to develop. One of the products is fatty acid. Enzymatic hydrolysis with lower pressure and temperature is the method to produce fatty acid. The aim of this research was to develop a kinetic of reaction of hydrolysis to produce fatty acid. The advantage of this research is obtaining an equation rate of enzymatic hydrolysis reaction which could be used to design a commercial scale reactor. A simple Michaelis-Menten model was used to obtain the equation of rate. By non-linear regression curve fitting the equation was tend to first order model, then linear and non-linear regression were utilized to the first order equation rate of reaction. The highest constant was of 0.07minute-1 which obtain from 40oC and w/o ratio of 1:2. Keywords: fatty acid, kinetic of hydrolysis